2006
DOI: 10.1179/174329406x150486
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thermochemical treatments on properties of maraging steels

Abstract: Effects of such thermochemical processes as carburising, nitriding and boriding on properties of maraging steel grades have been investigated. Despite certain improvements in the properties of the obtained surface, at present, carburising and boriding cannot be recommended owing to problems in the layer quality and difficulties in dimension control processes. Nitriding has proved to be the most suitable process and subsequent surfacing with a TiN layer on the previously nitrided substratum of maraging steel pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…with conformal channels. The steel acquires high hardness at the level of up to 52 HRC and competitive strength as compared to the standard material used for building injection and casting moulds [7]. In the analysis of the selected roughness parameters, it has been found that the higher from the base plate, the higher are the values of the parameters under consideration, from 32% to 85% for Ra and from 59% to 85% for Rz in comparison of the plate bottom to its top.…”
Section: Methodology Of Investigationmentioning
confidence: 99%
“…with conformal channels. The steel acquires high hardness at the level of up to 52 HRC and competitive strength as compared to the standard material used for building injection and casting moulds [7]. In the analysis of the selected roughness parameters, it has been found that the higher from the base plate, the higher are the values of the parameters under consideration, from 32% to 85% for Ra and from 59% to 85% for Rz in comparison of the plate bottom to its top.…”
Section: Methodology Of Investigationmentioning
confidence: 99%
“…Boron solubility in iron is very low and, according to Fe-B phase diagram [3], iron forms with boron two types of borides -FeB (16.25 wt.%) and Fe2B (8.48 wt.%), presence of which provides high hardness and wear resistance. Thermochemical boronising of metals has been extensively studied for various types of alloys, including maraging steels [4]. Laser boronising of steels and other alloys has not been studied so widely.…”
Section: Introductionmentioning
confidence: 99%
“…Maraging steels, having excellent weldability and high resistance to thermal fatigue due to the lack of carbon, has showed good suitability for SLM [1]. However, owing to the limited hardness and wear resistance, maraging steels has limited application at the harsh wear conditions [4]. In this study, the possibility to improve the surface characteristics of DIN 1.2709 steel SLM parts by application of laser alloying technology is evaluated.…”
mentioning
confidence: 99%
“…It is well known that nitriding can substantially increase the life span of conventionally processed tool inserts from maraging steel 41 , 42 . The positive effect of nitriding has also been reported for AM stainless steel 316L 43 .…”
Section: Introductionmentioning
confidence: 99%